Hunter perceptions toward chronic wasting disease: Implications for harvest and management - Jacob M. Haus; T. Brian Eyler; Mark D. Duda; Jacob L. Bowman (Wildlife Society Bulletin)
ABSTRACT Previous human dimension research has reported negative perceptions among hunters toward Chronic Wasting Disease (CWD) and disease‐related regulations that may limit hunter participation, reduce harvest, and generally complicate management. During 2013, we surveyed 1,524 Maryland, USA, deer (Odocoileus spp.) hunters from 3 counties of varying proximity to the Chronic Wasting Disease Management Area (CWDMA) regarding hunter behavioral changes due to CWD. We linked responses to each individual's harvest history to examine hunter retention, potential harvest reduction related to CWD presence and management, and degree to which distance from the disease affected behavior. Overall, 1.1% of respondents claimed to have stopped hunting because of CWD; however, 47.1% of those respondents continued to register deer after disease discovery, resulting in a true decrease in retention of no >0.6%. In the county containing the CWDMA, we observed the greatest percentage of negative perception (22.6%) and greatest reduction in harvest reportedly related to CWD (7.0%). In an adjacent county west of the CWDMA, we observed fewer negative perceptions (16.8%) and no reduction in harvest in response to disease discovery. Similar negative perceptions were reported in the county 200 km southeast of the CWDMA (14.1%), but also resulted in no reduction in harvest. Negative hunter perceptions did not seem to be directly related with hunter behavior. Behavioral shifts due to CWD were localized at the county scale and had less impact on annual harvest than normal year‐to‐year stochastic variability. Upon initial detection of CWD, we recommend implementing necessary protocols for disease management with the understanding that hunter perceptions may have negligible impact on harvest management. © 2017 The Wildlife Society.